2021
DOI: 10.1186/s12866-021-02187-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the invasion mechanism mediated by the outer membrane protein PagN of Salmonella Typhimurium

Abstract: Background Salmonella can invade host cells via a type three secretion system called T3SS-1 and its outer membrane proteins, PagN and Rck. However, the mechanism of PagN-dependent invasion pathway used by Salmonella enterica, subspecies enterica serovar Typhimurium remains unclear. Results Here, we report that PagN is well conserved and widely distributed among the different species and subspecies of Salmonella. We showed that PagN of S. Typhimuriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…The second invasion mechanism used by STm is a “zipper mechanism,” which requires a host membrane receptor. The interaction of the outer membrane proteins Rck and PagN with EGFR and proteoglycans/β1 integrin respectively, activates signaling pathways, involving GTPases and actin polymerization ( Lambert and Smith, 2008 ; Hume et al, 2017 ; Mambu et al, 2017 ; Barilleau et al, 2021 ). This mechanism is accompanied by a weaker remodeling of the membrane which is characteristic of a “zipper mechanism” ( Figure 2 ; Rosselin et al, 2010 ; Barilleau et al, 2021 ).…”
Section: Preferential Cell Type Targeted For Salmonella ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The second invasion mechanism used by STm is a “zipper mechanism,” which requires a host membrane receptor. The interaction of the outer membrane proteins Rck and PagN with EGFR and proteoglycans/β1 integrin respectively, activates signaling pathways, involving GTPases and actin polymerization ( Lambert and Smith, 2008 ; Hume et al, 2017 ; Mambu et al, 2017 ; Barilleau et al, 2021 ). This mechanism is accompanied by a weaker remodeling of the membrane which is characteristic of a “zipper mechanism” ( Figure 2 ; Rosselin et al, 2010 ; Barilleau et al, 2021 ).…”
Section: Preferential Cell Type Targeted For Salmonella ...mentioning
confidence: 99%
“…The interaction of the outer membrane proteins Rck and PagN with EGFR and proteoglycans/β1 integrin respectively, activates signaling pathways, involving GTPases and actin polymerization ( Lambert and Smith, 2008 ; Hume et al, 2017 ; Mambu et al, 2017 ; Barilleau et al, 2021 ). This mechanism is accompanied by a weaker remodeling of the membrane which is characteristic of a “zipper mechanism” ( Figure 2 ; Rosselin et al, 2010 ; Barilleau et al, 2021 ). Furthermore, studies using a STm mutant strain, which does not express Rck, PagN and a functional T3SS-1, reveal the existence of hitherto unidentified invasion factors causing weak or massive membrane rearrangements at distinct entry sites ( Rosselin et al, 2011 ; Roche et al, 2018 ).…”
Section: Preferential Cell Type Targeted For Salmonella ...mentioning
confidence: 99%
“…T3SS-1 enables the injection of bacterial effector proteins directly into the host cells, promoting actin polymerization and ruffling membrane rearrangements, thereby leading to bacterial internalization. This mechanism is known as the trigger mechanism and is widely dependent on host cells [ 106 ]. Postinfection, the incubation phase of the pathogen may not always be demonstrated by a symptomatic phase.…”
Section: Pathogenesis Of S Typhimentioning
confidence: 99%
“…PagN is an outer membrane protein that contributes to adhesion to and invasion of epithelial cells by Salmonella . The PagN as conserved gene is localized on the specific centisome 7 genomic island and widely distributed among the different Salmonella serovars [ 20 , 21 ]. The PagN is a PhoP-regulated gene that is up-regulated during growth within macrophages and in vivo in murine models of infection [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PagN is a PhoP-regulated gene that is up-regulated during growth within macrophages and in vivo in murine models of infection [ 22 ]. Some studies have shown that the PagN protein utilizes heparinated proteoglycans to adhere and invade mammalian cells [ 21 , 23 ]. The PagN protein contains a transmembrane region and four extracellular loops.…”
Section: Introductionmentioning
confidence: 99%